2009
DOI: 10.1364/oe.17.023332
|View full text |Cite
|
Sign up to set email alerts
|

Dual-channel all-optical wavelength conversion switching by four-wave mixing

Abstract: We report an experimental demonstration of dual-channel all-optical wavelength conversion switching in hot Rb vapor. In a four-level atomic system, a coupling field and a pump field interact with both (87)Rb and (85)Rb isotopes simultaneously and facilitate the generation of two nonlinear signals when the probe field is applied to the corresponding transition. Each nonlinear signal is switched on and off separately by the pump field at different frequencies based on four-wave mixing and isotope shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, so far most all-optical switching proposals are implemented as turning on or off one light beam by another light beam. In previous work [19], we have demonstrated two-pathway optical switching based on four-wave mixing (FWM) in hot rubidium vapour, in which both 87 Rb and 85 Rb atoms are driven into a doubleconfiguration so that two FWM signals are generated with different wavelengths. Here we report an experimental demonstration of multi-pathway optical switching and routing based on four-wave mixing and six-wave mixing (SWM) using the double-and triple-configurations in a Ne-buffered hot-rubidium cell.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far most all-optical switching proposals are implemented as turning on or off one light beam by another light beam. In previous work [19], we have demonstrated two-pathway optical switching based on four-wave mixing (FWM) in hot rubidium vapour, in which both 87 Rb and 85 Rb atoms are driven into a doubleconfiguration so that two FWM signals are generated with different wavelengths. Here we report an experimental demonstration of multi-pathway optical switching and routing based on four-wave mixing and six-wave mixing (SWM) using the double-and triple-configurations in a Ne-buffered hot-rubidium cell.…”
Section: Introductionmentioning
confidence: 99%
“…Antón et al proposed a method for optical switching with a technique based on controlled double-dark resonances [25,26]. Some of the above mentioned effects have been realized experimentally [27][28][29][30][31][32][33][34][35]. For instance, Yan et al [27] and Braje et al [28] demonstrated the Harris-Yamamoto scheme [15] in the Rb atomic system.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been proposed and demonstrated recently based on various physical mechanisms, such as optical bistability (OB) [1,2], electromagnetically induced transparency (EIT) [3,4], electromagnetically induced absorption (EIA) grating [5], wave mixing [6,7], two-photon absorption [8][9][10][11][12][13][14], and enhanced Kerr-nonlinearity [15]. However, most of those approaches are aimed at a binary switch, which has simple on/off states.…”
mentioning
confidence: 99%
“…All-optical switch, a device utilizing one optical field to control another, i.e., controlling light with light, is an essential component for the next generation of alloptical communication and computing, and has potential applications in quantum information networks. Many approaches have been proposed and demonstrated recently based on various physical mechanisms, such as optical bistability (OB) [1,2], electromagnetically induced transparency (EIT) [3,4], electromagnetically induced absorption (EIA) grating [5], wave mixing [6,7], two-photon absorption [8][9][10][11][12][13][14], and enhanced Kerr-nonlinearity [15]. However, most of those approaches are aimed at a binary switch, which has simple on/off states.…”
mentioning
confidence: 99%